Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1016/s0012-821x(98)00236-2
|View full text |Cite
|
Sign up to set email alerts
|

Magnetostratigraphy-based astronomical tuning of the early Pliocene lacustrine sediments of Ptolemais (NW Greece) and bed-to-bed correlation with the marine record

Abstract: Continental deposits from the early Pliocene lacustrine Ptolemais basin in NW Greece display rhythmical alternations of lignite and marl beds. Three parallel sections from this area are studied using magnetostratigraphy and cyclostratigraphy. The presence of the greater part of the Gilbert Chron enables the recognition of astronomical periodicities in the succession. Especially the precessional influence is evident, as it determines the lithological cycles. The continental Ptolemais composite section is correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
6

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 28 publications
3
51
0
6
Order By: Relevance
“…Recently, many Neogene Mediterranean records from widely different continental environments have been studied: from alluvial to lacustrine (Krijgsman et al, 1997;van Vugt et al, 1998;Steenbrink et al, 1999;Abdul Aziz et al, 2000;van Vugt et al, 2000). In this paper we present the results from one more continental section from southern Romania.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…Recently, many Neogene Mediterranean records from widely different continental environments have been studied: from alluvial to lacustrine (Krijgsman et al, 1997;van Vugt et al, 1998;Steenbrink et al, 1999;Abdul Aziz et al, 2000;van Vugt et al, 2000). In this paper we present the results from one more continental section from southern Romania.…”
Section: Introductionmentioning
confidence: 88%
“…The section contains some limestone beds of mainly pedogenic origin. van Vugt and Langereis (2000) reported that the thick (,25 m) sedimentary cycles have approximately the same period as precession. So, although the section contains coarse-grained siliciclastic sediment, the dominant period is not eccentricity but precession.…”
Section: Other Mediterranean Continental Basinsmentioning
confidence: 97%
See 2 more Smart Citations
“…Numerous studies across the Mediterranean postulate a climatic control on cyclical alternations in marine and terrestrial successions, invoking a linkage with the changeable variations in the Earth's orbital parameters (e.g. Postma & Drinia,1993;Weltje & De Boer, 1993;Kroon et al, 1998;Van Vugt et al, 1998;Wehausen & Brumsack, 1999;Foucault & Mélières 2000;Lourens et al, 2001;Joannin et al, 2007;amongst others). Therefore, it is likely that the sediments of Cyprus should provide a relatively intact archive of past climatic variability, likely to be recognizable on orbital timescales.…”
Section: Discussionmentioning
confidence: 99%